Go wild : free your body and mind from the afflictions of civilization - Ratey, John J., 1948- (Little, Brown and Company, 2014)
In GO WILD, Harvard Medical School Professor John Ratey, MD, and journalist Richard Manning reveal that although civilization has rapidly evolved, our bodies have not kept pace. This mismatch affects every area of our lives, from our general physical health to our emotional wellbeing. Investigating the power of living according to our genes in the areas of diet, exercise, sleep, nature, mindfulness and more, GO WILD examines how tapping into our core DNA combats modern disease and psychological afflictions, from autism and depression to diabetes and heart disease. By focusing on the ways of the past, it is possible to secure a healthier and happier future, and GO WILD will show you how.